Sensing Asymmetries in Other-than-human Forms. (September 2019) - Howe, Cymene
This essay is an examination of how sensing capacities can draw in, and from, other-than-human entities—both animate and inanimate. Based upon ethnographic field research in Iceland, it describes sensory encounters that are realizable through the bodies, sensations, and ontological status shifts of other beings and entities, namely, in bears and ice and earth. As anthropogenic impacts deepen, the essay argues, sensing ought to be practiced as a collaborative effort among human and other-than-human entities. Sensing by other means entails sensing through others' means and beyond the human sensorium.